2020
DOI: 10.1111/jgh.15312
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early stage gastric cancers in screening laser endoscopy using linked color imaging for patients with atrophic gastritis

Abstract: Background and Aims Laser endoscopy involves blue laser imaging in bright mode (BLI‐bright). Linked color imaging (LCI) is superior to white light imaging (WLI) for detecting gastric cancers. This study aimed to detect gastric cancers on screening endoscopy using not only WLI but also BLI‐bright and LCI in patients with atrophic gastritis. Patients and Methods A total of 500 patients with atrophic gastritis undergoing screening esophagogastroduodenoscopy were included. The gastric lumen was observed in the WLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Several case reports and studies have reported that LCI can more easily identify early-stage gastric cancer than the conventional white-light imaging (WLI) technique [13,14]. This has been further supported by recently published prospective studies, which have demonstrated that LCI has a higher detection ratio for gastric cancer than WLI [15][16][17]. The aim of this review was to summarize the current and future status of LCI as a diagnostic imaging method and describe its usefulness and challenges in clinical practice.…”
Section: Introductionmentioning
confidence: 94%
“…Several case reports and studies have reported that LCI can more easily identify early-stage gastric cancer than the conventional white-light imaging (WLI) technique [13,14]. This has been further supported by recently published prospective studies, which have demonstrated that LCI has a higher detection ratio for gastric cancer than WLI [15][16][17]. The aim of this review was to summarize the current and future status of LCI as a diagnostic imaging method and describe its usefulness and challenges in clinical practice.…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, gastric atrophy, intestinal metaplasia, enlarged folds and nodularity provide evidence of a gastric cancer risk [ 21 ]. In this regard, new endoscopic techniques, such as white-light imaging (WLI) and blue-laser imaging (BLI), have been considered to identify H. pylori status and gastric tumor lesions [ 22 - 24 ]. For instance, map-like redness by WLI or a cracked shape by BLI have been proposed as features of post-eradicated gastric mucosa polyps [ 18 , 19 ].…”
Section: Invasive Methodsmentioning
confidence: 99%
“…Beyond WLI and BLI, image-enhanced endoscopy (IEE), such as narrow-band imaging (NBI) or linked color imaging (LCI), with or without magnification, have also been introduced. Recent data have suggested increased diagnostic accuracy in the detection of gastrointestinal tumors with the application of these modalities during endoscopic examination [ 26 , 27 ]: NBI endoscopy has been introduced to improve the diagnosis of H. pylori -induced gastritis, preneoplastic lesions and early gastric cancer [ 28 ]; and LCI can be used to identify gastric intestinal metaplasia and, moreover, exhibits superiority to WLI for identifying H. pylori status and gastric tumors [ 22 , 24 , 29 ]. It is important to note, however, that IEE requires substantial training and a prolonged procedure time, while there are no uniform features of H. pylori infection in IEE [ 27 ].…”
Section: Invasive Methodsmentioning
confidence: 99%
“…[15][16][17] Linked color imaging (LCI) is a newly developed image-enhanced endoscopy (IEE) created by shortwavelength narrow-band laser light combined with white laser light, enabling brighter light in a distant area and enhancing color differences between red and white. 18,19 Accumulating evidence has shown that LCI is helpful not only for the diagnosis of pre-cancerous/cancerous lesions in the GI tract [20][21][22][23][24][25][26] but also for some inflammatory conditions such as reflux esophagitis, 27,28 Helicobacter pylori gastritis, 29 and ulcerative colitis. 30 However, the usefulness of this technology for the endoscopic diagnosis of EoE remains unclear.…”
Section: Introductionmentioning
confidence: 99%